ASSESSMENT OF HEAT RECOVERY AN RECOVERY EFFICIENCY OF A SEASONAL THERMAL ENERGY STORAGE IN A MOIST POROUS MEDIUM (Sciences & Technologie. B, Sciences de l'ingénieur, 2015)
Thermal energy storage has received a great interest by researchers and industrials as part of designing new systems able to store and deliver thermal energy efficiently for long periods. The aim of this preliminary work is to simulate performances of a promising seasonal heat storage system, which is a heat exchanger buried underground in a moist porous medium. Several case studies have been simulated according to different types of hot fluid carrier and moisture content in a porous medium. Comsol Multiphysics software was used to model heat exchange between a fluid carrier flowing through a GHX, and a partially saturated porous medium composed essentially of gravel and situated at about 0.5m underground. Numerical discretization was realized by finite elements method. System performances were evaluated for a one-year period in order to get a good estimation of long-term heat storage and recovery. The results showed that the use of gasoline as a working fluid will yield higher temperature levels than the other fluids especially during cold season; however, use of water allowed for the storage and recovery of bigger heat energy than gasoline or glycol can do. Furthermore, soil moisture content did not seem to have any influence the whole process.